IoT-based Communication Techniques of PVs Random Settlementin Residential Feeder - Rachmawati, Rachmawati (Jurusan Teknik Elektro Politeknik Negeri Lhokseumawe, 2022)
Whenever the additional random 1-5 kW rating and location photovoltaics (PVs) are connected into the residential feeder, the voltage profiles of the feeder become unbalanced. Besides the various load at the customer side has already imbalanced the feeder, the installed single-phase rooftop PVs do the same thing. They caused the power quality issues, namely voltage magnitude and angle, frequency, active and reactive powers become expressively recognized. Since the ancient electric utility infrastructure from power plants to customer side is now disrupting by the added settlement of several utility devices, the power quality issues have raisin significantly. This paper aims to implement the concept of several internets of things (IoT) technologies into the electric and communication infrastructures as they are able to virtuously cycle, enable, amplify and reinforce the utility development. To improve the imbalanced voltage and other power quality issues, this concept applied to the existed voltage regulation technique (VRT). The results show that the concept of IoT-based communication is successfully implemented if both the devices and technologies properly selected and designed. Additionally, the classification of communication layers, then the coordination of sensors, actuators, and meters along the residential feeder need to be considered as well.